Fraud recovery and the quality of country governance - Curti, Filippo; Mihov, Atanas (Journal of Banking & Finance, 2018)
Using supervisory data from U.S. financial institutions on fraud-related losses in foreign markets, we find that losses in countries with poor governance have lower recovery rates. Our results are robust to accounting for potential endogeneity and reverse causality concerns, among numerous robustness checks. The association is driven by intuitive governance dimensions such as control of corruption, rule of law, regulatory quality and government effectiveness. In addition, country governance plays a particularly important role in fraud recovery for firms with poor risk management quality. Overall, this paper presents unique and novel evidence tying country governance quality to firm-level risk realizations.